Impact of the 2020 COVID-19 pandemic on the workload of the orthopaedic service in a busy UK district general hospital. Issue 10 (October 2020) - Murphy, T.; Akehurst, H.; Mutimer, J.
Highlights: Since the outbreak of the COVID-19 pandemic orthopaedic departments have needed to adapt to focus only on essential activity in order to release resources. At our trust we had noted a reduction in the number of referrals made to our on-call trauma service since the outbreak was confirmed a pandemic. The mean number of referrals per week reduced by 33%. Total number of operative procedures per week reduced by 26%. The reduction in referrals was largely due to a reduction in the number of simple fractures; which may have been a result of social distancing measures. We hope that our observations may provide useful information when resource planning for future pandemic situations. Abstract: Introduction: The COVID -19 outbreak has had a profound effect on the management of healthcare service provision in the UK. Orthopaedic departments have been no exception to this and have needed to adapt to the changing circumstances by releasing resources and focusing on 'essential' activity. The aim of this study is to quantify the reduction in trauma and, in addition, describe any changes in the type of referrals to the trust which may have been affected by the pandemic itself and the social distancing measures employed by the UK government. Methods: : The study was performed in a UK District Hospital which is also a Trauma Unit providing trauma and orthopaedic care to a population of 625, 000 people. The trust based electronic database of trauma referrals was used to compare the numbers of, and types of referral to our trauma service during the COVID-19 pandemic and the corresponding time periods in the previous 3 years. Results: The mean number of referrals per week to the service reduced by 33% in the time period following the confirmation of the outbreak as a pandemic ( p <0.0001). Number of operations performed per week reduced by 26% ( p = 0.001). There was no change in the number of referrals relating to domestic abuse or non-accidental injury. In addition, numbers of hip fractures, periprosthetic fractures and prosthetic joint dislocations were unchanged. There was a significant reduction in the number of referrals for simple fractures, native joint dislocations, wounds and soft tissue injuries. Within the paediatric population, similarly, a reduction in simple fracture referrals was demonstrated. Discussion: An association between the outbreak of the pandemic and a reduction in referral numbers to our department has been demonstrated. The direct cause of this may be multifactorial but proposing that it is, in part, due to the social distancing measures introduced by the government is certainly conceivable. The patterns of injury would reflect this also with low energy and fragility trauma persisting whilst injuries associated with younger people have reduced. We would suggest that information such as this could be useful in healthcare planning and resource allocation in future pandemic situations.